2002
DOI: 10.1002/cne.10423
|View full text |Cite
|
Sign up to set email alerts
|

Localization of neuropeptide Y1 receptor immunoreactivity in the rat retina and the synaptic connectivity of Y1 immunoreactive cells

Abstract: Neuropeptide Y (NPY), an inhibitory neuropeptide expressed by a moderately dense population of wide-field amacrine cells in the rat retina, acts through multiple (Y1-y6) G-protein-coupled receptors. This study determined the cellular localization of Y1 receptors and the synaptic connectivity of Y1 processes in the inner plexiform layer (IPL) of the rat retina. Specific Y1 immunoreactivity was localized to horizontal cell bodies in the distal inner nuclear layer and their processes in the outer plexiform layer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…Y 1 receptor-ir was detected in cell bodies in the distal and proximal INL ( Figure 1 (cb)), arrows). A previous study has identified these cells as horizontal and amacrine cells ( D’Angelo et al., 2002 ). In accordance, we also detected Y 1 -ir processes ramifying in strata 2 and 4 of IPL.…”
Section: Resultsmentioning
confidence: 99%
“…Y 1 receptor-ir was detected in cell bodies in the distal and proximal INL ( Figure 1 (cb)), arrows). A previous study has identified these cells as horizontal and amacrine cells ( D’Angelo et al., 2002 ). In accordance, we also detected Y 1 -ir processes ramifying in strata 2 and 4 of IPL.…”
Section: Resultsmentioning
confidence: 99%
“…In the sensory retina of the rat, Y1‐like immunoreactivity is expressed by neurons but not by glial cells (D'Angelo et al, 2002). We used tetrodotoxin to discriminate whether the swelling‐relevant Y1 receptors are expressed by neuronal or glial cells.…”
Section: Resultsmentioning
confidence: 99%
“…In rat retina, we and others have detected the presence of mRNAs for NPY Y 1 , Y 2 , Y 4 and Y 5 receptors (Alvaro et al, 2007;D'Angelo and Brecha, 2004). The NPY Y 1 receptor-IR was found to be localized in horizontal and amacrine cell bodies and processes (D'Angelo et al, 2002).…”
Section: Localization Of Npy and Npy Receptors In The Retinamentioning
confidence: 67%
“…On the other hand, when applied exogenously, NPY stimulates the release of (Bruun and Ehinger, 1993). These results and the presence of NPY in amacrine cells (in the INL) and displaced amacrine cells (in the GCL), which may connect with other amacrine cell subtypes and ganglion cells that are not immunoreactive for NPY, suggest that NPY may also play a role as a neuromodulator in the inner retinal layers (D'Angelo et al, 2002;Oh et al, 2002)".…”
Section: Modulatory Effects Of Npy In the Retinamentioning
confidence: 81%
See 1 more Smart Citation